Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1007/s00253-012-4227-5
|View full text |Cite
|
Sign up to set email alerts
|

Selective breeding for desiccation tolerance in liquid culture provides genetically stable inbred lines of the entomopathogenic nematode Heterorhabditis bacteriophora

Abstract: The entomopathogenic nematode (EPN) Heterorhabditis bacteriophora is used in biological plant protection to control pest insects. In the past, several attempts targeted at an enhancement of the desiccation tolerance of EPN by genetic selection in order to improve their storage stability. The subsequent loss of improved beneficial traits after release of selection pressure has often been reported. In order to stabilize progress of selective breeding, selection during liquid culturing was tested against propagat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…Thus, Bai et al, (2005) proposed that EPN producers develop numerous inbred lines from promising candidate populations, and then select the lines that exhibit high levels of desirable traits for commercialization. In a variation of the Bai et al, (2005) approach, Anbesse, Sumaya, Dörfler, Strauch, and Ehlers (2013) reported that multiple heterorhabditid inbred lines can be created during liquid culture. Given that heterorhabditids cannot mate in liquid culture, all progeny are produced by selfing (via hermaphrodites) , which results in automatic creation of multiple inbred lines.…”
Section: Improved Methods Of Applicationmentioning
confidence: 98%
“…Thus, Bai et al, (2005) proposed that EPN producers develop numerous inbred lines from promising candidate populations, and then select the lines that exhibit high levels of desirable traits for commercialization. In a variation of the Bai et al, (2005) approach, Anbesse, Sumaya, Dörfler, Strauch, and Ehlers (2013) reported that multiple heterorhabditid inbred lines can be created during liquid culture. Given that heterorhabditids cannot mate in liquid culture, all progeny are produced by selfing (via hermaphrodites) , which results in automatic creation of multiple inbred lines.…”
Section: Improved Methods Of Applicationmentioning
confidence: 98%
“…Gaugler & Campbell, 1991;Gaugler, Campbell, & McGuire, 1989;Hiltpold et al, 2010a;Hiltpold, Toepfer, et al, 2010 (Gaugler & Campbell, 1991;Gaugler et al, 1989) or other particular behaviors (Bal, Michel, & Grewal, 2014), virulence (e.g., Peters & Ehlers, 1998;Tomalak, 1994), tolerance to extreme temperatures (e.g., Ehlers, Oestergaard, Hollmer, Wingen, & Strauch, 2005;Shapiro, Glazer, & Segal, 1997;Susurluk, Ulu, & Kongu, 2013) and desiccation (e.g., Anbesse, Sumaya, Dörfler, Strauch, & Ehlers, 2013;Strauch, Oestergaard, Hollmer, & Ehlers, 2004). While selective breeding offers an efficient and relatively quick method to obtain EPN populations with desired or improved traits (discussed in Chap.…”
Section: Use/selection For a More Competitive Species Or Populationmentioning
confidence: 98%
“…Despite superior performances, native and adapted EPN populations may still fail in controlling pest populations under harsh conditions in their natural environment. Previous studies have demonstrated that genetic selection of EPNs can overcome certain physiological limitations by improving various traits of particular interest for biological control such as host finding (e.g., or other particular behaviors (Bal, Michel, & Grewal, 2014), virulence (e.g., Peters & Ehlers, 1998;Tomalak, 1994), tolerance to extreme temperatures (e.g., Susurluk, Ulu, & Kongu, 2013) and desiccation (e.g., Anbesse, Sumaya, Dörfler, Strauch, & Ehlers, 2013;Strauch, Oestergaard, Hollmer, & Ehlers, 2004). While selective breeding offers an efficient and relatively quick method to obtain EPN populations with desired or improved traits (discussed in Chap.…”
Section: Use/selection For a More Competitive Species Or Populationmentioning
confidence: 99%